(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Keywords: Black pepper; meristem culture; Piper nigrum; shoot regeneration; root induction Bangladesh j. genet. biotechnol. 7 (1&2): 91-93, 2006 (June & December)